Real Time Data Processing and Analysis in MIS: Challenges and Solutions - Talukdar, Jubayeer Ahmed (Journal of Research in Science and Engineering, 2025)
Real-time data processing and analysis play a crucial role in modern Management Information Systems (MIS), enabling organizations to make informed decisions swiftly. However, this process comes with its challenges, ranging from data volume to processing speed and data quality. This research paper examines the challenges faced in real-time data processing and analysis in MIS and proposes solutions to address these challenges. The paper covers topics such as data streaming, scalability, latency management, data quality assurance, security, integration with existing systems, visualization, machine learning integration, and regulatory compliance. By understanding these challenges and implementing appropriate solutions, organizations can harness the power of real-time data to enhance decision-making processes and gain a competitive edge.